The integration of the self-concept-based Upanishad learning model in blended learning and its impact on character development and creative thinking skills - Suwendra, I Wayan; Suarnaya, I Putu; Widiana, I Wayan; Asli, Ni Luh (Journal of Education and e-Learning Research, 2023)
The aim of this research is to investigate the impact of a self-concept-based Upanisad learning model integrated in mixed learning on the building of character and creative thinking skills. This study adopted a quasi-experimental design with a posttest-only control design. The population of the study consisted of 90 students. A random sampling technique was used to take the samples which consist of 60 students. Tests and questionnaires were used as data collection methods. The test instruments used were a description test with 10 items and a questionnaire with a total of 30 items. The analysis technique employs MANOVA in SPSS. The results showed that learning with the self-concept based Upanisad learning model simultaneously or partially impacts character and creative thinking skills. The results show that students who are taught using the self-concept based Upanisad learning model gain mean scores in character and creative thinking skills. Moreover, other results show that learning with the self-concept based Upanisad learning model is more influential on students’ character than their ability to think creatively. Based on these conclusions, the researcher recommended that a self-concept-based Upanishad learning model be able to be used as an innovative learning model for improving character and creative thinking skills.